KERAGAMAN SECARA MOLEKULER BAKTERI ASAM LAKTAT PADA ILEUM DAN SEKUM AYAM BROILER YANG DIBERI PERLAKUAN PAKAN HASIL FERMENTASI Chrysonilia crassa - Husnul Khotimah; Siti Nur Jannah; Rejeki Siti Ferniah (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2017)
Lactic Acid Bacteria (LAB) are microflora in the digestive tract that has positive roles in poultry’s health. The amount and diversity of LAB in the gastrointestinal tract are influenced by several factors, one of them is by the feeding factor. The study aims to analyze the LAB diversity in ileum and cecum after feeding of fermented Chrysonilia crassa molecularly. Analysis of LAB spesies diversity is needed to provide a baseline profile of microbial community database on the illeum and cecum digestive tract of broiler chicken between control (commercial feed) and treatment (feed by Chrysonilia crassa fermentation) by the method of Terminal Restriction Fragment Length Polymorphism (T-RFLP). The calculated values are the number of phyilotypes, relative abundance, Shannon-Wiener (H') diversity index, evenness (E), and similarity. Group of LAB detected in the control were Lactobacillus delbrueckii (180 bp), Lactobacillus sp. (187 bp), Lactobacillus plantarum (572 bp), uncultured bacterium (87 bp) and unidentified (50 bp, 582 bp). The result of this study showed that by giving the fermented feed by Chrysonilia crassa had resulted in the decreasing of LAB diversity in ileum (0.66), cecum (0.48) compared with commercial feed (control) in ileum (0.84), cecum (1.05). Keywords: broiler chicken, cecum, ileum, LAB, T-RFLP